Analysis of Finger Print Usage at Wachid Hasyim Foundation I to Improve Employee Work Discipline - Dwi Hardaningtyas; Nur Holifah (NeoRespublica : Jurnal Ilmu Pemerintahan, 2023)
The use of the Automatic Finger Print Identification System (AFIS) attendance is the first step to assist educators and educational staff in terms of attendance. The purpose of this research is to analyze the use of finger print at the Wachid Hasyim 1 Surabaya Foundation. The research method used is descriptive qualitative method. The results of this study indicate that the Wachid Hasyim 1 Surabaya Foundation applies finger print attendance to improve employee work discipline, by requiring education and teaching staff to record attendance every working day. This policy is followed by regulations that are not allowed to change attendance unless proven by a letter from the principal, and nominal remuneration will be received every month, according to online attendance recorded via a fingerprint attendance machine